2018
DOI: 10.1177/0284185118780897
|View full text |Cite
|
Sign up to set email alerts
|

Endovascular thrombectomy in anterior circulation stroke and clinical value of bridging with intravenous thrombolysis

Abstract: Background Bridging treatment with intravenous thrombolysis (IVT) before endovascular thrombectomy (EVT) in acute ischemic stroke is applied under the assumption of benefits for patients with large vessel occlusion (LVO). However, the benefit of this additional step has not yet been proven. Purpose To compare procedural parameters (procedural time, number of attempts), complications, and clinical outcome in patients receiving EVT vs. patients with bridging treatment. Material and Methods In this prospective st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 32 publications
1
13
0
Order By: Relevance
“…17 The Japanese guidelines state that stroke patients with severe renal disorder should be given IVT cautiously. 20 In our patient's case, the clinical presentation suggested LVO, and waiting for the coagulation test results would have delayed the patient's treatment; therefore, we bypassed IVT and went directly to MT. There is no need to wait for renal function test results before IVT.…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…17 The Japanese guidelines state that stroke patients with severe renal disorder should be given IVT cautiously. 20 In our patient's case, the clinical presentation suggested LVO, and waiting for the coagulation test results would have delayed the patient's treatment; therefore, we bypassed IVT and went directly to MT. There is no need to wait for renal function test results before IVT.…”
Section: Discussionmentioning
confidence: 85%
“…A study showed that the prognosis after direct MT in patients with LVO is not inferior to that of patients who received IVT as bridging therapy before MT. 20 In our patient's case, the clinical presentation suggested LVO, and waiting for the coagulation test results would have delayed the patient's treatment; therefore, we bypassed IVT and went directly to MT. In general, IVT is not a contraindication for patients with renal insufficiency in AIS.…”
Section: Discussionmentioning
confidence: 85%
“…Many studies, in fact, did not reveal any difference between the two treatments. [14][15][16][17][18][19][20][21][22] On the whole the available studies are based on small samples of patients, the larger study being the Catalonia analysis, including 1166 patients. 18 On the basis of data from a recent meta-analysis, 26 assuming an alpha of 0.05 and beta of 0.2, a total sample of 408 patients would be needed to detect a 12% absolute difference in 90-day death or severe dependency, and 962 patients to detect a 9.7% absolute difference in functional independence at three months.…”
Section: Discussionmentioning
confidence: 99%
“…Observational retrospective analyses gave conflicting results: while some of them suggested a benefit of IVT pretreatment, [9][10][11][12][13] in terms of higher rate of recanalization, shorter duration of the endovascular procedure, lower number of passes of the thrombectomy device per patient, or better clinical outcome, others did not find significant differences between the two approaches. [14][15][16][17][18][19][20][21][22] A pooled analysis 23 of the STAR 24 and SWIFT 25 trials suggested that treatment with IVT before MT does not add any clinical benefit as compared to MT alone. Conversely, two meta-analyses carried out on subgroups of patients included in the available randomized clinical trials, 26 and on available observational and randomized studies 27 showed that bridging therapy leads to a lower probability of death or serious disability as compared to MT alone.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation